Development of The Vistori Book on Basic Concepts of Division for Grade II Elementary School Students - Davina Aurelia; Yulia Linguistika; Goenawan Roebyanto; Ni Luh Sakinah Nuraini (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
In elementary school, the use of textual learning media, which can help improve literacy dan students’ ability to understand stories, is still limited, especially when it is integrated with mathematics. This study aims to create a visual book that explores the fundamental concept of division in second-grade elementary school and evaluates its validity. The ADDIE model, which consist of five phases such as analysis, design, development, implementation, and evaluation, was used in this study. In this research, data collection involved the utilization of interviews, questionnaires, and documentation. Expert validation and student responses were used to determine the score. The result showed that vistori book have excellent qualifications for both validity and attractiveness. Based on the analysis, vistori book that cover the basic concept of division for second-grade elementary school are suitable for use in teaching and learning.